Religion, State and Human Rights: Negotiating Accommodation Limits in the Constitutional Court - Rumadi, Rumadi (Madania: Jurnal Kajian Keislaman, 2020)
One of crucial issue in Muslim countries, not except Indonesia, is relation between religion and the state. Even though Pancasila and the 1945 Constitution  were claimed as a final, but it did not necessarily mean that position of religion, state and human rights is final and clear.  The negotiation between religion, state and human rights not only on political forum like at The House of Representative, but also in Constitutional Court  session. There are debates and opinion contestations. The problem is what is the politics of law accommodation towards religious aspirations, which the Constitutional Court has built through its decisions and arguments? Through analysis on two issues: 1) freedom of religion and belief; and 2) marriage law, this article argues that Constitutional Court’s decision, especially relation between religion, state and human rights not only based on law consideration, but also on non-law consideration. Regarding private law, the Constitutional Court opened a fairly wide accommodation, so that more religious aspects would be accommodated by the state even with limited reforms. The limit of accommodation is an Islamic criminal law that cannot be made exclusively for Muslims. The accommodation of Islamic criminal law is only possible if the norms are incorporated into the national criminal law through a process of rational objectification. Based on this argument, continuous negotiation and contestation between religion, state and human rights will go on since Indonesia is not a religious state, which is based only on one religion, nor a secular state, which does not consider religion at all. Salah satu isu krusial di negara Muslim, tidak terkecuali Indonesia, adalah relasi agama dan negara. Meskipun Pancasila dan Undang-Undang Dasar 1945 dinyatakan final, namun bukan berarti kedudukan agama, negara, dan hak asasi manusia sudah final dan jelas. Perundingan antara agama, negara dan hak asasi manusia tidak hanya di forum politik seperti di Dewan Perwakilan Daerah (DPR), tapi juga di sidang Mahkamah Konstitusi. Ada perdebatan dan kontestasi pendapat. Persoalannya, bagaimana politik akomodasi hukum terhadap aspirasi agama yang dibangun Mahkamah Konstitusi melalui putusan dan dalilnya? Melalui analisis terhadap dua isu: 1) kebebasan beragama dan berkeyakinan; dan 2) hukum perkawinan, pasal ini berpendapat bahwa putusan Mahkamah Konstitusi khususnya hubungan antara agama, negara dan hak asasi manusia tidak hanya berdasarkan pertimbangan hukum, tetapi juga pertimbangan non hukum. Terkait hukum privat, Mahkamah Konstitusi membuka akomodasi yang cukup luas, sehingga lebih banyak aspek keagamaan yang diakomodasi oleh negara meski dengan reformasi yang terbatas. Batasan akomodasi adalah hukum pidana Islam yang tidak dapat dibuat secara eksklusif untuk Muslim. Akomodasi hukum pidana Islam hanya dimungkinkan jika norma-norma tersebut dimasukkan ke dalam hukum pidana nasional melalui proses objektifikasi yang rasional. Berdasarkan argumen ini, negosiasi dan kontestasi yang terus menerus antara agama, negara dan hak asasi manusia akan terus berlangsung karena Indonesia bukanlah negara agama yang hanya didasarkan pada satu agama, bukan pula negara sekuler, yang sama sekali tidak mempertimbangkan agama.